Enhancing Environmental Literacy Through Experiential and Joyful Learning-Marine Edutourism: Implementation in Indonesia and Malaysia - Hayati, Riza Sativani; Ma'rifah, Destri Ratna; Astutik, Julia; Prayogo, Fika Enggar (FKIP Universitas Lampung, 2025)
Enhancing Environmental Literacy Through Experiential and Joyful Learning Marine Edutourism: Implementation in Indonesia and Malaysia. Objectives: Low environmental literacy among students necessitates innovative methodologies in environmental education. One effective approach is the development of an environmental learning model designed to enhance environmental literacy. Indonesia and Malaysia, both rich in marine resources, also possess significant potential for marine tourism. Marine tourism sites can be utilized as valuable resources for marine environmental learning, thereby improving environmental literacy in the domain of issue analysis. Environmental education is integrated into tourism, called marine edutourism. Marine edutourism developed a learning model by combining joyful and experiential learning concepts, which was then referred to as Experiential and Joyful Learning Marine Edutourism (EJoy-ME). This research aims to develop and implement the EJoy-ME learning model to enhance students' environmental literacy in Indonesia and Malaysia. Methods: The research method is Design and Developmental Research consisting of six phases: (1) problem identification; (2) objectives description; (3) design & develop the artifact; (4) artifact test (implementation); (5) evaluate; (6) results communication. Findings: This research successfully implemented the EJoy-ME learning model in Wakatobi National Park, Indonesia; Mangrove Point, Klang River, Malaysia; and Kuala Selangor Nature Park, Malaysia. The results show that this model enhances students' environmental literacy in the domain of issue analysis, both in Indonesia and Malaysia; however, implementation in Wakatobi showed the most significant improvement in increasing environmental literacy. The issue analysis skills of 160 trial subjects increased with moderate criteria in the EJoy-ME model but remained low in the PBL model. The N gain score showed that the increase in issue analysis was quite effective in the EJoy-ME model. Student responses to the seven assessed aspects were also very good, namely experiential learning, joyful learning, understanding of the material, environmental education, learning motivation, and practicality of the model. Conclusion: The implementation indicates that EJoy-ME is a feasible environmental education learning model, effective in enhancing environmental literacy in the domain of issue analysis. Keywords: marine edutourism, environmental literacy, joyful learning, experiential learning.